Changes in Peasant Children’s Reading Practices and Living Conditions in Dnieper Ukraine at the Turn of the 19th–20th Centuries - Voloshenko , Viktoriia (Studia Historiae Oeconomicae, 2023)
The article analyzes the reading practices and living conditions of Ukrainian peasant children as a social phenomenon. The children’s reading modes in the family system and social distribution of household duties and leisure activities are presented. Herein characterized are the specific features of reading training in the period of modernization transformations against the background of the urbanization processes; post-reform emancipation; public life’ politicization; and increasing volumes of information required for the reorganization of the lifestyle. The author shows the gradualness of changes in view of economic problems, the close connection between reading practices and oral culture; the lack of educational institutions, the inertia in public perceptions of the social position of the peasantry, and the assessment of social perspectives for the self-realization of literate villages. It was found that despite the unfavorable circumstances, there was an increase in the pace of peasants’ awareness of the importance of literacy for their children in the future. New reading practices contributed to the transformation of the private sphere of young people, personal independence, and individualization of life scenarios.